Hubble : imaging space and time - DeVorkin, David H., 1944-; Smith, Robert W. (Robert William), 1952- (Washington, D.C. : Smithsonian National Air and Space Museum : In association with National Geographic, 2008)
Contains full-color images captured by the Hubble Space Telescope and discusses the telescope's development and how it works.
The most famous telescope -- The realm of the Nebulae -- Into orbit -- Observing with Hubble -- The wonder of outer space / by Elizabeth Kessler -- The harvest.
Includes bibliographical references and index.
Keywords: Hubble Space Telescope (Spacecraft); Astronomy -- Pictorial works; Space astronomy -- Pictorial works